Contribution of large-pore channels to inflammation induced by microorganisms - Vega, José L.; Gutiérrez, Camila; Rojas, Mauro; Güiza, Juan; Sáez, Juan C. (Frontiers in Cell and Developmental Biology, 2023)
Plasma membrane ionic channels selectively permeate potassium, sodium, calcium, and chloride ions. However, large-pore channels are permeable to ions and small molecules such as ATP and glutamate, among others. Large-pore channels are structures formed by several protein families with little or no evolutionary linkages including connexins (Cxs), pannexins (Panxs), innexin (Inxs), unnexins (Unxs), calcium homeostasis modulator (CALHM), and Leucine-rich repeat-containing 8 (LRRC8) proteins. Large-pore channels are key players in inflammatory cell response, guiding the activation of inflammasomes, the release of pro-inflammatory cytokines such as interleukin-1 beta (IL-1ß), and the release of adenosine-5’-triphosphate (ATP), which is considered a danger signal (Chekeni et al., 2010; Crespo et al., 2017). This review summarizes our current understanding of large-pore channels and their contribution to inflammation induced by microorganisms, virulence factors or their toxins.